Probe beam deflection studies of nanostructured catalyst materials for fuel cells - García, Gonzalo (2008)
Probe beam deflection (PBD) techniques, both as cyclic voltadeflectometry (CVD) and chronodeflectometry (CD), were applied for the first time to the study of the electrochemistry of nanostructured Pt materials which are commonly used as electrocatalysts in fuel cells. The electrochemical surface reactions, including faradaic processes, double layer charging and specific anion adsorption were easily detected. Quantitative analysis of the chronodeflectometric data made possible to elucidate the dynamics of double layer charging in such materials and to determine the potential of zero charge (pzc) of the metal present either as a monolithic mesoporous material or as metal nanoparticles supported on carbon. The electro-oxidation of CO, adsorbed on nanostructured Pt, was also studied by CVD and CD being able to detect the formation of CO2 and H3O+ related with the nucleation and growth process which controls the rate of CO stripping. The interplay of Pt oxide formation and COad electrooxidation, both in potential and time, was detected indicating possible application of the technique to other electrocatalysts.